Geophysical field theory and method. - Kaufman, Alexander A., 1931-2023 (International geophysics series ;, 1994)
This book contains information about the theory of electromagnetic fields in conducting mediums. It describes the theoretical foundation of electromagnetic methods used in all areas of exploration geophysics, including a study of deep layers of Earth. This book will be useful for research and exploration geophysicists, electronic engineers, and graduate and university geophysics departments. Key Topics Covered Include: . Electromagnetic fields in conducting media . Physical principles of electromagnetic methods applied in geophysics . Relationship between electromagnetic fields and parameters of a medium.